Kateheza kot pomoč umetni inteligenci - Vodičar, Janez (Bogoslovni vestnik, 2024)
Artificial intelligence is already present in almost every aspect of modern life. In the field of education, its negative impact on students is often emphasized. In this article, however, we also show the positive aspects of integrating AI into educational work. It is even more difficult to show the positive aspects of AI in the catechetical field, even though this area is included in the new “Directory for Catechesis”. As we show in this article, catechesis can also contribute to a safer and more humane use of AI in the field of general education. We show this by presenting the latest movements advocating the pedagogical use of AI and comparing them with the general aims of catechesis. The results of these comparisons are also compared with the latest manuals for Slovenian catechesis in the fourth and fifth grades of elementary school. The results show that the contribution of catechesis in the field of education for openness and educability can be the basis for a successful positive application of AI in the wider pedagogical space.
Keywords: artificial intelligence; catechesis; educability; education; inteligentnost; intelligence; izobraževanje; kateheza; oznanilo; proclamation; učljivost; umetna inteligenca